2011
DOI: 10.3341/kjo.2011.25.6.459
|View full text |Cite
|
Sign up to set email alerts
|

Horner's Syndrome with Abducens Nerve Palsy

Abstract: A 68-year-old male patient presented with a week of sudden diplopia. He had been diagnosed with nasopharyngeal cancer 8 months prior and had undergone chemotherapy with radiotherapy. Eight-prism diopter right esotropia in the primary position and a remarkable limitation in abduction in his right eye were observed. Other pupillary disorders and lid drooping were not found. After three weeks, the marginal reflex distance 1 was 3 mm in the right eye and 5 mm in the left eye. The pupil diameter was 2.5 mm in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…This peculiar association has been noted earlier in ICA aneurysm, nasopharyngeal carcinoma, metastatic neoplasms, caroticocavernous fistula and trauma 4,5 This presentation in a primary CNS tumour has not been reported previously. With this case report we would like to highlight that unilateral 6th nerve palsy with ipsilateral Horner's Syndrome is rare, and should prompt investigation for underlying cavernous sinus etiology.…”
Section: Case Reportmentioning
confidence: 88%
“…This peculiar association has been noted earlier in ICA aneurysm, nasopharyngeal carcinoma, metastatic neoplasms, caroticocavernous fistula and trauma 4,5 This presentation in a primary CNS tumour has not been reported previously. With this case report we would like to highlight that unilateral 6th nerve palsy with ipsilateral Horner's Syndrome is rare, and should prompt investigation for underlying cavernous sinus etiology.…”
Section: Case Reportmentioning
confidence: 88%
“…[3][4][5][6][7] In our small series of five cases we found two meningiomas, one carotid-cavernous aneurism, 1 foreign body (bullet) and a squamous cell carcinoma as responsible for PS. Neuroimaging (MRI, CT and Angiography) confirmed the initial clinical diagnostic showing cavernous sinus lesions in all our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Top Karti et al 14 reported a case of a 62-year-old man who was diagnosed with nasopharyngeal carcinoma 10 years prior to onset of horizontal binocular diplopia which was the first sign of a recurrence of the disease. Kang et al 15 described a 68-year-old man who had a known diagnosis of nasopharyngeal carcinoma and presented with a sixth nerve palsy and a sequential ipsilateral Horner’s syndrome. The patient died 15 months later.…”
Section: Discussionmentioning
confidence: 99%